Comparative study between stapler hemorrhoidectomy and open hemorrhoidectomy - Batheja, Sagar; Mhaske, Ashok; Dausage, Chirag (International Surgery Journal, 2025)
Background: Hemorrhoids are very common condition, affecting approximately 1 in 4 individuals. The open hemorrhoidectomy, also known as the Milligan Morgan hemorrhoidectomy, is the gold normal for treating third- or fourth-degree hemorrhoids, The stapler hemorrhoidectomy was successfully introduced with enthusiasm because it is associated with low level of postoperative discomfort. The clinical result of stapler hemorrhoidectomy and open hemorrhoidectomy was compared in this research based on post-operative problems and return to regular activities. Methods: This potential observational analytical study was led on 80 patients diagnosed with grade II-IV hemorrhoids over 18 months. Patients were owed into group A (OH, n=30) and group B (SH, n=50) based on surgeon in consultation with the patient after usual counselling. The above study arms group were studied and compared. Results: Stapler hemorrhoidectomy demonstrated significant advantages, severity of pain was documented to be significantly lower, reduced hospital stay (2.06±0.77 days versus 3.57±0.73 days), earlier return to normal activities (1.82±0.75 versus 3.03±1.16), rate of complications in the form of pain and bleeding were significantly lower during 1st week and second week of follow up. Conclusions: When compared to open hemorrhoidectomy, stapler hemorrhoidectomy has a better clinical outcome because it is linked to fewer postoperative complications, especially pain and bleeding, early bowel movements, early hospital discharge, and an early return to normal activities. To determine the incidence of recurrence after stapler haemorrhoidectomy, further clinical studies with long-term follow-up are necessary.